Mobile agents in distance education - Srikanthan, K. (2008)
The educational phenomenon has been changing rapidly along with the drastic changes in society. Distance Education is not a new phenomenon. We are experiencing dramatic interest and activity in computer-mediated distance education. In response various innovative trials have been launched that use the multimedia communications technologies to assist the distance education applications. These technologies can provide more attractive solutions for the educational society by fulfilling their greater expectations on their educational needs. In the other hand it will also create more challenges in organizing information and facilitating its efficient retrieval. From the network prospective there will be additional challenges in meeting bandwidth requirements and network management. Mobile software agent technology, which has emerged as an important new area of research, possesses many of the attributes required to address the above-mentioned challenges. However few applications are found to take advantages of mobile agents. This dissertation explores the suitable deployment areas of mobile agent in the context of distance education applications. Based on this analysis, a framework of a mobile agent system is proposed to support the aspects of distance education applications more efficiently.